Biphasic and triphasic dose responses in zebrafish embryos to low-dose 150 kV X-rays with different levels of hardness. (3rd August 2016) - Kong, Eva Yi; Cheng, Shuk Han; Yu, Kwan Ngok
Abstract: The in vivo low-dose responses of zebrafish ( Danio rerio ) embryos to 150 kV X-rays with different levels of hardness were examined through the number of apoptotic events revealed at 24 h post fertilization by vital dye acridine orange staining. Our results suggested that a triphasic dose response was likely a common phenomenon in living organisms irradiated by X-rays, which comprised an ultra-low-dose inhibition, low-dose stimulation and high-dose inhibition. Our results also suggested that the hormetic zone (or the stimulation zone) was shifted towards lower doses with application of filters. The non-detection of a triphasic dose response in previous experiments could likely be attributed to the use of hard X-rays, which shifted the hormetic zone into an unmonitored ultra-low-dose region. In such cases where the subhormetic zone was missed, a biphasic dose response would be reported instead.